Raw Multi-Channel Seismic Shot Data from the Greenland Margin acquired during R/V Maurice Ewing expedition EW9607 (1996) ... - Holbrook, W. (Interdisciplinary Earth Data Alliance (IEDA), 2012)
This data set was acquired with the LDEO Multi-Channel Seismic system during R/V Maurice Ewing expedition EW9607 conducted in 1996 (Chief Scientist: Dr. W. Steven Holbrook). These data files are of SEGY format and include Multi-Channel Reflection Seismic shot data that have not been processed. Data were acquired as part of the projects: Seismic Investigation of the Greenland Margin (SIGMA) and Deep Structure of a Hotspot Influenced Rifted Volcanic Margin: A Joint U.S.-Danish Seismic Experiment off SE Greenland, and funding was provided by NSF grant: OCE94-16631. These data are cited by Dahl-Jensen et al., 1997, Hopper et al., 2003, Korenaga et al., 2000, and Holbrook et al., 2001. ...